ANALISIS NILAI PELANGGAN YANG MEMPENGARUHI LOYALITAS (STUDI KASUS PADA BANK KBPR JETIS PONOROGO) - Mashariono Mashariono; Hening Widi Oetomo (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2006)
Retail Banking (BPR) in Jetis Ponorogo has interest in its business survival partly because of the high loyalty of its customers. Therefore, it is essential to know what factors influence the customer’s loyalty. The appropriate method for addressing the above-mentioned problem is factor analysis. Data collected from a sample of 155 respondents and there are 12 variables used in this study. The results are from 12 variables, all of them are usable and grouped into five new factor based on eigen value more than 1 (> = 1). The five factors are: Humane Products Factor has eigen value of 2,597 with variant percentage of 21,643%; Trust Factor has eigen value of 2,096 with variant percentage of 17,463%; Sincerity Factor has eigen value of 1,536 with variant percentage of 12,797%; Hospitality Factor has eigen value of 1,261 with variant percentage of 10,506%; Professionalism Factor has eigen value of 1,067 with variant percentage of 8,888%. From correlation matrix, we get value from Bartlett’s Test of Sphericity (BTS) of 433,290, which suggest that on correlation matrix there are correlation between factors supported by Kaiser-Meyer-Olkin (KMO) value of 0,606 and variant cumulative value of 71,298%.Based on the results, it is suggested that it would be better for the company to develop some humane product factor analyzed in this study because it is the predominant factor in affecting the customers’ loyalty. The customers’ loyalty is an important factor in guarantee the survival of Retail Banking (BPR) in Jetis Ponorogo.